2004
DOI: 10.1177/0743558403258860
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Future Orientation, Impulsive Sensation Seeking, and Risk Behavior Among Adjudicated Adolescents

Abstract: Because of high levels of risk behavior, adjudicated adolescents are at high risk for negative health outcomes such as nicotine and drug addiction and sexually transmitted diseases. The goal of this article is to examine relationships between future orientation and impulsive-sensation-seeking personality constructs to risk behaviors among 300 adjudicated adolescents. Significant relationships between impulsive sensation seeking and future orientation were found for several risk behaviors. Individuals with more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
264
3
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(287 citation statements)
references
References 55 publications
12
264
3
8
Order By: Relevance
“…Although some differences are intuitive, others may provide important points of divergence. For example, hard drug abstainers are likely to be significantly lower on sensation seeking than those who frequently use hard drugs (Robbins & Bryan, 2004). However, little is known about groups that are less clearly distinct; for instance, how do experimenters (time-limited use) and moderate users (who maintain use) differ with regard to impulsive personality and externalizing behaviors?…”
Section: Covariates Of Substance Usementioning
confidence: 99%
“…Although some differences are intuitive, others may provide important points of divergence. For example, hard drug abstainers are likely to be significantly lower on sensation seeking than those who frequently use hard drugs (Robbins & Bryan, 2004). However, little is known about groups that are less clearly distinct; for instance, how do experimenters (time-limited use) and moderate users (who maintain use) differ with regard to impulsive personality and externalizing behaviors?…”
Section: Covariates Of Substance Usementioning
confidence: 99%
“…They live in their fantasies and are highly interested in socializing with their peers to be able to accept familial and social responsibilities. According to Robbins and Bryan study, a positive attitude toward the future reduces the adolescents' tendency to use drugs and alcohol and engage in high-risk sexual behavior (18). A tendency toward independence in adolescence is another cause for discord between parents and children.…”
Section: Discussionmentioning
confidence: 99%
“…A fairly large body of research has focused on identifying potential factors associated with recidivism among male young offenders 8,9,10 . Consequently, there has been a lack of attention to female offenders 11,12,13 , especially in Brazil, including information about recidivism by gender.…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of young offenders placed in correctional facilities are diagnosed with a mental health disorder, and most reported that they were under the influence of alcohol or drugs when they committed the delinquent act that led to their current detainment 10,22,23 . In addition, it has been emphasized that the characteristics and recidivism of female young offender populations have been understudied, yet require distinct attention 11 .…”
Section: Introductionmentioning
confidence: 99%